Decadal data reveal declines, not species replacement, of salamanders under agrarian reform - Jan W. Arntzen (Global Ecology and Conservation)
Long-term data are uniquely suited to test hypotheses on processes in ecology, contemporary biogeography and conservation. I tested for species replacement among crested and marbled newts (genus Triturus) in western France, for which historical data showed a mutual range shift of 1 km per year. Triturus population sizes were estimated in 23 ponds from 1979 to the present. The data show a massive amphibian decline from pond infilling, succession and neglect, arising from the agrarian transition from cattle to arable farming. In eight persisting ponds, Triturus populations declined in unmanaged ponds and were stable in two managed ponds. Species composition was stable or changed in either direction. The absence of further notable species replacement is in line with population isolation by less dispersal from fewer and smaller populations in a thinning network of ponds. It is concluded that the large-scale agrarian reform that progressed over the post-World War II period intervened with, and eventually frustrated the original aim of the research project.